News Commentaries January - December 1986 - Abrahams, Peter (My University, 1986)
News Commentaries Broadcast in 1986
194 pgs. Typed scripted, Letter-sized, Sepia-Toned, in fairly good condition.
Keywords: Jamaica - Politics and government; Gangsters - Jamaica; Business enterprises - Black; Developing countries - Economic policy.; Democracy - Jamaica - History - 20th century; Constitutions - Jamaica.; Peace movements - Jamaica; People's National Party (PNP); Jamaica Labour Party (JLP)